IMPROVING UNIVERSITY STUDENTSâ READING COMPREHENSION USING GRAPHIC ORGANIZERS - Rumiris, Juella (Jurnal Dinamika Pendidikan, 2014)
This study was a classroom action research aimed to improve EFL tertiary studentsâ reading comprehension by using graphic organizer, one of teaching methods used universally to help learners to understand reading deeper, especially for retelling story outcome.The participants were 44 undergraduate students attending the researcher Reading II class. The improvement in this study was focused on the participantsâ skills of determining main idea, identifying topic, summarizing, and enriching vocabulary. To check studentsâ comprehension, the researcher measured the studentsâ reading comprehension using open-ended questions in written form, interview, as well as rubrics which are presented in both quantitative and qualitative data. The results revealed that there was no significant improvement in the participantsâ main idea identification and vocabulary enrichment skills. However, there was robustly significant improvement in their topic identification and summarizing skills.Keywords : graphic organizer, reading comprehension, main idea, topic, summarizing